VIRTUAL REALITY BASED ON NATIONAL HEROES INTRODUCTION (CASE STUDY: SDN SRENGSENG 04 PAGI) - Tjahjono, Budi; Arradh Khan, Muzammil; Dewi Ariessanti, Hani; Verdiana Latif, Dini (International Journal of Psychosocial Rehabilitation, 2020)
National Hero is a title given to Indonesian citizens who fought against the fallen colonialism in defense of the Indonesian nation and state. Basically elementary school children only know the heroes from textbooks on social science subjects. The problem faced by the teacher when explaining the material is that students are easily bored following the subject because the teacher only tells the history of the hero without anything interesting. One solution to create a learning process that is fun and not bored by making the delivery of information can be delivered more interactively and feels more real because it can reach the human senses, for example is VR (Virtual Reality) technology. The goal is to achieve a strong sense of presence in the virtual environment. Especially in the classroom, with that technology can be utilized in the classroom that is Virtual Reality Recognition of national heroes. By using the Prototype method, users can play an active role in the development of the system to be created. From the description of the problem above the appropriate method is to use the PIECES method. Where the results of the PIECES method can save time, get information that is more quickly absorbed when students use this application, students do not need to go to the location.